Science, strategy and war : the strategic theory of John Boyd - Osinga, Frans P. B. (Cass series--strategy and history, 2007)
By highlighting diverse sources that shaped Boyd?s thinking, and by offering a comprehensive overview of his work, this volume demonstrates that the common interpretation of the meaning of Boyd?s OODA loop concept is incomplete.